Neuropathic and cerebrovascular correlates of hearing loss in Fabry disease - Ries, Markus; Kim, H. J.; Zalewski, C. K.; Mastroianni, M. A.; Moore, D. F.; Brady, R. O.; Dambrosia, J. M.; Schiffmann, R.; Brewer, C. C. (Brain, 2007)
Fabry disease, OMIM 301500, is a progressive multisystem storage disorder due to the deficiency of α-galactosidase A (GALA). Neurological and vascular manifestations of this disorder with regard to hearing loss have not been analysed quantitatively in large cohorts. We conducted a retrospective cross sectional analysis of hearing loss in 109 male and female patients with Fabry disease who were referred to and seen at the Clinical Center of the National Institutes of Health, Bethesda, MD, USA on natural history and enzyme replacement study protocols. There were 85 males aged 6-58 years (mean 31 years, SD 13) and 24 females aged 22-72 years (mean 42 years, SD 12). All patients underwent a comprehensive audiological evaluation. In addition, cerebral white matter lesions, peripheral neuropathy, and kidney function were quantitatively assessed. HL95, defined as a hearing threshold above the 95th percentile for age and gender matched normal controls, was present in 56% [95% CI (42.2-67.2)] of the males. Prevalence of HL95 was lower in the group of patients with residual GALA enzyme activity compared with those without detectable activity (33% versus 63%) HL95 was present in the low-, mid- and high-frequency ranges for all ages. Male patients with HL95 had a higher microvascular cerebral white matter lesion load [1.4, interquartile range (IQR) 0-30.1 ± versus 0, IQR 0-0], more pronounced cold perception deficit [19.4 ± 5.5 versus 13.5 ± 5.5 of just noticeable difference (JND) units] and lower kidney function [creatinine: 1.6 ± 1.2 versus 0.77 ± 0.2 mg/dl; blood urea nitrogen (BUN): 20.1 ± 14.1 versus 10.3 ± 3.28 mg/dl] than those without HL95 (P < 0.001). Of the females, 38% had HL95. There was no significant association with cold perception deficit, creatinine or BUN in the females. Word recognition and acoustic reflexes analyses suggested a predominant cochlear involvement. We conclude that hearing loss involving all frequency regions significantly contributes to morbidity in patients with Fabry disease. Our quantitative analysis suggests a correlation of neuropathic and vascular damage with hearing loss in the males. Residual GALA activity appears to have a protective effect against hearing loss.
Published: 14 November 2006
Gesehen am 15.05.2019